REFLECTION OF CLOUD COMPUTING ON IMPROVING FINANCIAL ACCOUNTING SYSTEM: AN ANALYTICAL STUDY OF OPINIONS OF A SAMPLE OF EMPLOYEES IN COMMERCIAL BANKS (World Economics and Finance Bulletin, 2024)
The current research aims to reveal the reflection of cloud computing on improving the financial accounting system among a sample of workers in commercial banks, and the study adopted the management of the questionnaire in order to measure the level of availability of its variables, and on this basis the study relied on the statistical package of the program (SPSS.V.28) in order to extract the results using the arithmetic mean, standard deviation, correlation coefficient, and impact factor, and therefore the study has reached a set of results stated in Cloud computing can help improve the financial accounting system of commercial banks, as cloud computing provides a common, scalable and rapidly adaptable information infrastructure, which can lead to improved efficiency and effectiveness in managing banking operations and improving financial performance. Commercial banks can use cloud computing services to solve large data storage and processing problems, This allows them to analyze data faster and more accurately, improve risk management and address fraud and financial fraud, and the study also made a set of recommendations, the most important of which It is also important to emphasize that cloud computing allows commercial banks to reduce costs and large investments in IT infrastructure, as commercial banks can rely on the existing cloud infrastructure to meet their technological needs..
Keywords: cloud computing; financial accounting system; commercial banks